1997
DOI: 10.2307/2998643
|View full text |Cite
|
Sign up to set email alerts
|

Interest Group Survival: Shared Interests Versus Competition for Resources

Abstract: SURVIVING AS AN ORGANIZED INTERESTIn order to survive, an organization must effectively exploit the resources in its environment. Because many organizations are dependent on the same resources as other, similar, organizations, they must find a way to share resources or eliminate other organizations through competition. In the case of interest groups working toward the same goal or collective good, however, competition seems illogical. How do interest groups resolve this conflict between selfpreservation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Early entrants were able to establish a niche for themselves and did not decline even after competition effects should have set in. Haider-Markel (1997) showed that organizations for gays and lesbians avoided direct competition with each other, and as a consequence the expansion of one organization led to growth in others.…”
Section: Deterministic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early entrants were able to establish a niche for themselves and did not decline even after competition effects should have set in. Haider-Markel (1997) showed that organizations for gays and lesbians avoided direct competition with each other, and as a consequence the expansion of one organization led to growth in others.…”
Section: Deterministic Factorsmentioning
confidence: 99%
“…
Past analyses of organizational failure and success include studies of traditional social movements (Sandell, 2001;Stern, 1999), interest organizations Lowery, 1995, 1997;Haider-Markel, 1997;Nownes and Lipinski, 2005), and new social movements (Edwards and Marullo, 1995;Minkoff, 1993Minkoff, , 1997. Most of these, however, focus exclusively on factors outside the organization' s control or on organizational design and strategy.
…”
mentioning
confidence: 99%
“…Previous studies have approached the formation of issue niches as a yes or no question; either groups form niches or they do not Haider-Markel, 1997). This approach is consistent with Browne's (1990) argument that all groups seek to pursue issue niches.…”
Section: Lobbying and Identitymentioning
confidence: 99%
“…Scholars have focused on the questions of whether the macro-structures of policy domains are balkanized (e.g., Baumgartner & Leech, 2001;Haider-Markel, 1997;Nownes, 2000) and whether the desire to form issue niches is a strategic motivator at the group level (e.g., Heaney, 2004;Hojnacki, 1997). However, the question of how interest groups build their identities on Capitol Hill has been subject to relatively little scrutiny.…”
mentioning
confidence: 99%
“…Browne (1990) introduced the idea that groups strive to differentiate themselves in Washington by establishing a balkanized niche 'characterized by obsessive focus on a single facet' of policy (p. 489). A host of empirical evidence has accumulated to show that groups indeed gravitate toward issues and policy domains that are sparsely populated so that they may have a greater impact on the policy process Lowery, 1996, 1997;Hojnacki, 1997;Haider-Markel, 1997;Heaney, 2004a). Heaney (2004bHeaney ( , 2014 goes so far as to show that one of the primary strategic functions of an interest group is to create unique identity as a way to maximize their perceived policy expertise and to minimize competition.…”
mentioning
confidence: 97%